The Effect of Health Education about Check Breast Self (SADARI) on Adolescent Motivation in Early Detection of Breast Cancer - Andi Ria Metasari; Nurlina (International Journal of Public Health Excellence (IJPHE), 2022)
Breast cancer is the most feared disease by women. Even breast cancer has attacked teenagers. One of the first steps to prevent breast cancer is to provide health education to adolescents to increase awareness in doing breast self-examination (BSE). If BSE can be done regularly, then breast cancer can be detected early. This study aims to determine the effect of health education on BSE on adolescent motivation in early detection of breast cancer in Polewali Village, Tanete Riattang Barat District, Bone Regency. The research design used was quasi-experimental with one group pretest post-test method . The research sample amounted to 40 people with purposive sampling technique in accordance with the inclusion criteria. The results of the study based on the Wilcoxon test obtained a p value of 0.000 (<0.5) meaning that there was an effect of health education on BSE on adolescent motivation in efforts to detect breast cancer early. There was an increase in the motivation of adolescents to do breast self-examination before and after the provision of health education so that there was a significant effect of health education in increasing the motivation of adolescents to perform breast self-examination (BSE). For this reason, it is necessary to collaborate between the regional government related to health workers to obtain information about health, especially reproductive health in adolescents.